Роль тамкара в Вавилонии II и I тыс. до н.э. - Дандамаев, M. A. (1973)
Dandamajev, M. A.; The role and functions of the tamkārī in Babylonia in the Second and first Millennia B.C.; engl. Résumé S. 225-227.